Report of Cosmic-Ray and Balloon Observations by the 11th Japanese Antarctic Research Expedition in 1969-1971 - Masahiko KUSUNOSE; Masahiro KODAMA (National Institute of Polar Research, 1973)
To explore the solar cycle dependence of the latitude effect of cosmic ray intensity, measurements of the nucleon and muon intensities were carried out using the super neutron monitor 3-NM-64 and the cubical meson monitor aboard the icebreaker FUJI, during the period from November 25, 1969 to May 8, 1970. Six plastic balloons (5,000m3) were launched from Syowa Station during January to February 1970. Four of them were made for observation of auroral X-rays and two flights for the low energy proton and alpha particles. On February 11, 1970, an event of distinct solar X-ray burst was observed in the course of auroral X-ray measurement at a height of 7 mb. The continuous observation of cosmic ray neutron intensity at Syowa Station has been made using the super neutron monitor 12-NM-64 since February 1969. In February 1970, a cubical meson monitor (effective area: 4m2) was newly constructed by the use of plastic scintillators as detector and the lead producer of the neutron monitor as absorber. The barometric pressure coefficients were found to be 0.74 %/mb and 0. 16 %/mb for the neutron and meson components, respectively. A solar cosmic ray event of order of 10^9 eV was observed by two set of the super neutron monitors, aboard FUJI and at Syowa Station, on January 24-25, 1971. An appreciable deviation of the observed barometric pressure due to high winds and its influence on the pressure-corrected cosmic ray intensity were investigated using the data of neutron component. Collection of cosmic dust was tried at Syowa Station with the filtration method for water which was made from iceberg, as well as for air.